The relationship between renal cell carcinoma and nuclear retinoid/rexinoid receptors - Lenko, Vladimir; Bialesova, Lucia; Macejova, Dana; Bujdak, Peter; Breza, Jan; Brtko, Julius (Biomedical papers, 2013)
Background: Renal cell carcinoma (RCC) is a urologic malignancy with a steady rise in incidence and high mortality rate. Between 60 to 70% of patients with renal cell carcinoma can only be cured with surgery but despite advances in early diagnostis, in around 20-30% of cases there is metastasis. For these patients, chemotherapy and radiotherapy are ineffective and hence the prognosis is poor. Retinoids are biologically active compounds of either natural or synthetic origin that are involved in complex physiological and developmental processes in many tissues including cell proliferation and activation of tumour suppression genes. This article reviews the role of retinoids and their cognate nuclear retinoid/rexinoid receptors in relation to renal cell carcinoma.Methods: A literature search using ScienceDirect and Medline with a focus on the relationship between renal cell carcinoma and nuclear retinoid/rexinoid receptors.Results: Use of retinoids/rexinoids in the treatment of locally advanced and metastatic RCC significantly prolongs median time of tumour progression and overall survival of patients. Combination therapy with other preparations has greater efficacy than treatment with retinoids alone. Patient survival can be predicted on the basis of the expression of different all-trans retinoic acid receptor (RAR) and 9-cis retinoic acid receptor (RXR) subtypes.Conclusions: Since nuclear retinoid receptors play a crucial role as ligand-activated, DNA binding, trans-acting, transcription-modulating proteins involved in a general molecular mechanism responsible for transcriptional responses in target genes, retinoids might be an alternative approach for the treatment of renal cell carcinoma.
Keywords: renal cell carcinoma; retinoids; rexinoids; nuclear receptors; chemoprevention